Interacción de los suelos sulfatados ácidos con el agua y sus efectos en la sobrevivencia del bocachico (Prochilodus magdalenae) en cultivo - Pardo Carrasco, Sandra C.; Suárez Mahecha, Héctor; Pertuz Buelvas, Vicente M. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Aquaculture in coastal areas grows rapidly. For fish ponds construction, soil is dug and used as material for the conformation of dikes, frequently originating the exposure of Acid Sulphate Soils (ASS) containing extreme acidity, a saturation percentage less than 50% and exchangeable aluminum higher than 5 Cmol+Kg-1. When ASS is exposed to air, iron pyrite (FeS2) oxidizes (FeSO4) and produces H2SO4whose dissociation in water reduces pH values inferior to 4. Flooded SSA may have a pH between 5 and 7; nevertheless, when they are drained and exposed to air pH drops to 2 or 3. A 1.5ha pond was built in the municipality of Cotorra (Córdoba), removing and exposing soil. Then, it was flooded with wetland water (pH 6.5; OD 3 mg/l; alkalinity 120 mg/l) and cultured with 10.000 bocachico alevins; an hour later, all fish were dead. In order to determine the possible cause of death, soil, water and gills were analyzed. The soil analysis showed an ASS with acid pH, high content of organic matter and high levels of S, Fe and Mn. Water analysis showed a lethal pH for most of the fish; likewise Fe, Al and CO2 levels were above acceptable maximum. Microcirculatory alteration in gill’s lamellar was found. It is suggested that the cause of death of bocachicos was the acidity of water due to the Na+/H+ exchange inhibition in gills caused by H+ and Al+ excess. This situation affected the permeability of gill epithelium increasing the loss of ions and the alteration of osmoregulation. It is evident that ASS absorb and release nutrients, exchanging substances with water and, this way, affecting their quality.